Marketing activities to promote the subjects of management of sports events of international level - Попов [Aleksandr Popov], Олександр Вікторович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> 1024x768 <![endif]--> Done identify the organizational and managerial conditions integrated marketing activities for the improvement of the sports events with international standards. Presents a comprehensive description of the conditions and management of marketing activities of entities conducting sports events of international level, which is the result of analysis of the literature, document analysis, systems analysis, survey. Established that a comprehensive marketing activities of sports organizations currently constrained by the difficulty of theoretical and practical ideas. Retrieved reason for the development and implementation of integrated organizational and management model of marketing activities of the sports events with international standards. Consider the interests of different groups, organizational and administrative conditions for cooperation of different actors in a framework providing integrated marketing sports events. <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->